Knowledge management - Nádvorník, Pavel; Mládková, Ludmila, 1963-; Nedzelský, Roman; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
The main goal of this thesis is to describe implementation of the information system that will support knowledge management using KM-Beat-it methodology in Helpdesk department of the Wincor Nixdorf, Ltd. company. Due to lack of knowledge management principles usage this system will support procedures and processes of knowledge management. Setup and implementation of this system was performed using and combining of two methodologies, methodology for knowledge management implementation KM-Beat-it and Waterfall methodology, that describes information systems development process. There was information system implemented in organization that meets its objective. It was implemented in Operations department in the first phase. Based on feedback from users and optimization of the system it will be implemented also in remaining departments of the organization.
Vedoucí práce: Ludmila Mládková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses